2014
DOI: 10.1063/1.4862274
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast carrier dynamics in CuInS2 quantum dots

Abstract: The ultrafast carrier dynamics in CuInS2 (CIS) quantum dots (QDs) was studied by means of femtosecond transient absorption (TA) spectroscopy. The size-dependent 1S transition energy determined from bleaching spectra is in agreement with that calculated on the finite-depth-well model in the effective mass approximation. The TA bleaching comes from filling of electron quantized levels, allowing us to know the dynamics of the 1S electron in CIS QDs. The sub-100-ps electron trapping at surface defects in bare QDs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
57
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 18 publications
13
57
0
2
Order By: Relevance
“…The relaxation of the 1S states is faster in smaller QDs with larger density of carriers at surface, because the surface trapping rate is proportional to the existing probability of carriers at the QD surface. 28,39 Therefore, surface traps provide local sites for fast relaxation of the photoexcited excitons, mainly resulting in a short PL-lifetime in smaller CIS QDs with shorter-wavelength emission. We investigated the PL kinetics of the CIS QDs before and after shell growth to further understand the luminescence mechanism underlying the extrinsic impurities, as shown in Fig.…”
Section: Time-resolved Pl Spectroscopy Of Cis Qds and Cis/zns Core/shmentioning
confidence: 99%
See 1 more Smart Citation
“…The relaxation of the 1S states is faster in smaller QDs with larger density of carriers at surface, because the surface trapping rate is proportional to the existing probability of carriers at the QD surface. 28,39 Therefore, surface traps provide local sites for fast relaxation of the photoexcited excitons, mainly resulting in a short PL-lifetime in smaller CIS QDs with shorter-wavelength emission. We investigated the PL kinetics of the CIS QDs before and after shell growth to further understand the luminescence mechanism underlying the extrinsic impurities, as shown in Fig.…”
Section: Time-resolved Pl Spectroscopy Of Cis Qds and Cis/zns Core/shmentioning
confidence: 99%
“…In our previous work, we found that the electron trapping at surface defects increased with decreasing the QD size which significantly reduced the carrier lifetimes of small CIS QDs. 28 The different relaxation behavior was due to the size inhomogeneity in CIS QDs. The relaxation of the carriers is faster in smaller QDs because of the larger density of states of electrons and holes at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to off-stoichiometry defects in the bulk, surface states are also found to play a significant role in carrier trapping for CuInS 2 QDs, 4 , 16 , 24 which reduces charge separation efficiencies in related photovoltaic and photocatalytic devices. Coating QDs with another material to form core/shell hetero QDs has been an effective approach to mitigating surface trapping states.…”
Section: Introductionmentioning
confidence: 99%
“…The photoluminescence of Cu-rich CIS QDs originates from the recombinations of electrons and holes trapped in the defect states (Fig. [48][49][50] Furthermore, we measured the PLQY of NIRemitting QDs, which have an emission peak at 718.6 nm, using rhodamine B 49 to conrm the reliability of the PLQY determined with rhodamine 6G. 43 The PLQY of the QDs was determined by comparing the total emission intensity of the QDs with that of rhodamine 6G at an excitation wavelength of 500 nm.…”
Section: Resultsmentioning
confidence: 99%